Evaluation of topical oclacitinib and nail trimming as a treatment for murine ulcerative dermatitis in laboratory mice - Steven E. Davison; Kathryn M. Emmer; Beatrice Ugiliweneza; Leslie C. Sherwood (PLoS ONE, 2022)
Murine ulcerative dermatitis (UD) is a common, multifactorial skin disease of C57BL/6 and C57BL/6-background strains of mice. Many treatment options have been previously reported but have been variably successful and may interfere with specific research studies. Janus kinase (JAK) inhibitors, such as oclacitinib, have been used to treat allergic dermatitis in humans, dogs, and other species. Additionally, topical oclacitinib was shown to improve an induced model of dermatitis in mice. We hypothesized that topical application of oclacitinib in conjunction with hind limb nail trimming would improve UD lesion scores more than our institutional standard treatment regime using meloxicam, topical antibiotic ointment, and nail trimming or nail trimming alone. To test this, mice with naturally occurring UD were recruited to the study and assigned to one of three treatment groups (n = 14/group): nail trim only; nail trim plus meloxicam and topical triple antibiotic ointment; or nail trim plus topical oclacitinib. UD was assessed on days 1, 7, and 14 for all treatment groups, and scored based on a previously published scoring system that quantitatively scored UD lesions based on pruritus, character of the lesion, size of lesion, and location of lesion. Here we found that mean UD scores decreased from day 1 to day 7 and from day 1 to day 14 for all treatment groups. However, there was no significant difference in mean UD score between the treatment groups at any timepoint. These data show that topical oclacitinib and nail trimming together improved UD lesion scores comparably to our institutional standard treatment and nail trimming alone. However, further studies may be warranted to investigate other potential applications of oclacitinib to treat UD.